(untitled) (Web of Teachers: Inderscience Research, 2025)
In modern society, the success of interpersonal communication largely depends on adherence to communication culture and rules of effective interaction. This paper analyzes the use of non-standard tests in developing communication skills. The advantages of interactive, role-based, and emotional-intellectual test formats are demonstrated alongside traditional methods for assessing and enhancing communication culture.